Legal Protection of Third Parties in Credit Agreements with Liability Guarantee - Kurniasari, Mei Ayu; Hasana, Dahniarti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the implementation of mortgage agreements in Semarang Regency, to find out and analyze legal protection for third parties in Credit Agreements with Mortgage Guarantees in Semarang Regency, and to find out and analyze examples of mortgage deed. The research approach method used in this thesis is a sociological juridical research method. This research specification uses descriptive analysis. The type of data used in this research is primary data which includes the 1945 Constitution; Act No. 2 of 2014; Mortgage Laws; Code of Civil law; the Criminal Code, as well as secondary data containing books and other supporting documents. Research data collection with interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is a qualitative analysis of the interactive model as proposed by Miles and Huberman. The results of the study indicate that the implementation of credit with mortgage guarantees at the bank has a procedure regarding the provisions, the conditions that must be carried out from the time the customer's application is submitted until the loan is paid off by the bank. Legal protection for third parties in the implementation of mortgage guarantee objects is regulated in Article 1 paragraph (1) No. 8 of 1999 concerning the Consumer Protection Act.